Comparative Transcriptome, Metabolome, and Ionome Analysis of Two Contrasting Common Bean Genotypes in Saline Conditions - Niron, Harun; Barlas, Nazire; Salih, Bekir; Türet, Müge (Frontiers in Plant Science, 2020)
Soil salinity is a major abiotic stress factor that limits agricultural productivity worldwide, and this problem is expected to grow in the future. Common bean is an important protein source in developing countries however highly susceptible to salt stress. To understand the underlying mechanism of salt stress responses, transcriptomics, metabolomics, and ion content analysis were performed on both salt-tolerant and susceptible common bean genotypes in saline conditions. Transcriptomics has demonstrated increased photosynthesis in saline conditions for tolerant genotype while the susceptible genotype acted in contrast. Transcriptome also displayed active carbon and amino-acid metabolism for the tolerant genotype. Analysis of metabolites with GC-MS demonstrated the boosted carbohydrate metabolism in the tolerant genotype with increased sugar content as well as better amino-acid metabolism. Accumulation of lysine, valine, and isoleucine in the roots of the susceptible genotype suggested a halted stress response. According to ion content comparison, the tolerant genotype managed to block accumulation of Na+ in the leaves while accumulating significantly less Na+ in the roots compared to susceptible genotype. K+ levels increased in the leaves of both genotype and the roots of the susceptible one but dropped in the roots of the tolerant genotype. Additionally, Zn+2 and Mn+2 levels were dropped in the tolerant roots, while Mo+2 levels were significantly higher in all tissues in both control and saline conditions for tolerant genotype. The results of the presented study have demonstrated the differences in contrasting genotypes and thus provide valuable information on the pivotal molecular mechanisms underlying salt tolerance.